2017
DOI: 10.1103/physrevlett.118.243201
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Magnetization of a Dense Molecular Gas with an Optical Centrifuge

Abstract: Strong laser-induced magnetization of oxygen gas at room temperature and atmospheric pressure is achieved experimentally on the sub-nanosecond time scale. The method is based on controlling the electronic spin of paramagnetic molecules by means of manipulating their rotation with an optical centrifuge. Spin-rotational coupling results in high degree of spin polarization on the order of one Bohr magneton per centrifuged molecule. Owing to the non-resonant interaction with the laser pulses, the demonstrated tech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
2
20
1
Order By: Relevance
“…This stability of superrotor rotations with respect to collisions was indeed observed experimentally with nitrogen and oxygen superrotors at ambient conditions [10,12,13,18]. Classical simulations of a gas of superrotors show that, while the high rotation rates are conserved initially, they rapidly relax towards thermal equilibrium once the rotational-translational energy exchange becomes relevant [19,20].…”
Section: Introductionsupporting
confidence: 67%
“…This stability of superrotor rotations with respect to collisions was indeed observed experimentally with nitrogen and oxygen superrotors at ambient conditions [10,12,13,18]. Classical simulations of a gas of superrotors show that, while the high rotation rates are conserved initially, they rapidly relax towards thermal equilibrium once the rotational-translational energy exchange becomes relevant [19,20].…”
Section: Introductionsupporting
confidence: 67%
“…For highly rotating states, the centrifugal force may lead to the stretching of bonds [35] or even to dissociation [32]. Furthermore, it has been shown that an ensemble of superrotors is stable against collisions [34,36,37], which allows to measure the spinrotation coupling [38], the interaction with a magnetic field [39][40][41] or may also cause magnetization in an ensemble of paramagnetic superrotors [42].…”
Section: Introductionmentioning
confidence: 99%
“…The timedependent magnetization creates a current in a pick-up coil (2 mm diameter, 5 mm long, 4.5 turn) through the voltage (EMF), which is used to determine the number of spin-polarized atoms generated by the photodissociation, similar to recent experiments by Milner et al in the measurement of electron-spin-polarized O 2 molecules. [14]. We vary the photodissociation laser intensity by several orders of magnitude, by drastically changing the focusing conditions, and show that nearly all of the molecules in the laser focus can be dissociated, leading to densities of 10 19 cm −3 .…”
mentioning
confidence: 96%